2014
DOI: 10.1002/ejic.201402494
|View full text |Cite
|
Sign up to set email alerts
|

How Counterions Affect the Solution Structure of Polyoxoaurates: Insights from UV/Vis Spectral Simulations and Electrospray Mass Spectrometry

Abstract: The solution structure of the two presently known polyoxoaurates, [ (Au 4 Se 4 ), was elucidated by a combination of time-dependent density-functional-theory (TD-DFT) calculations, experimental UV/Vis spectroscopy, and electrospray ionization mass spectrometry (ESI-MS). The TD-DFT-predicted electronic spectra for molecular models including different numbers of counterions, along with the main Au 4 As 4 and Au 4 Se 4 structural motifs, were analyzed and compared with the experimental UV/Vis spectra of the two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…On the other hand, it is rather a challenging task to determine the exact species involved in the equilibria; therefore, it is unlikely that the predominant species and the properties of POMs can be checked quickly. Spectroscopic techniques, such as UV/Vis and NMR spectroscopy, can be used to determine roughly the species and stabilities of POMs in solution. However, the sensitivities of these techniques are poor, and large amounts of samples are required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is rather a challenging task to determine the exact species involved in the equilibria; therefore, it is unlikely that the predominant species and the properties of POMs can be checked quickly. Spectroscopic techniques, such as UV/Vis and NMR spectroscopy, can be used to determine roughly the species and stabilities of POMs in solution. However, the sensitivities of these techniques are poor, and large amounts of samples are required.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospray ionization mass spectrometry (ESI‐MS) is an alternative method. However, it is difficult to determine the dynamic equilibria of POMs in solution . Therefore, the development of a simple and efficient method that can be used to monitor the solution behavior of POMs in real time is urgently demanded.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that the ability of copper to adopt distinct coordination arrangements [35] and the sterics of small monodentate ligand anions play a crucial role in the construction of monomeric vs. extended structures in the presence of the sulfur source. In contrast to the situation in the cubane-like complexes of Co II and Ni II featuring "free" thiane tails, [21] the thiane unit of HL·S can effectively coordinate to the trigonalbipyramidal Cu II ions with higher affinity to sulfur in 2 to afford 1D polymeric chains with weak antiferromagnetic exchange interactions between the central copper atoms.…”
Section: Discussionmentioning
confidence: 99%
“…The observed {Cu 4 O 4 (PO 4 ) 4 } constituents are isostructural to the arsenate‐capped polyoxoaurate (POAu) with the formula [Au III 4 O 4 (AsO 4 ) 4 ] 8− (Figure c). As shown in Figure d, two [Au III 4 O 4 (AsO 4 ) 4 ] 8− polyoxoanions intercalate five Na + ions to afford the [Na 5 Au III 8 O 8 (AsO 4 ) 8 ] 11− composition present in solution and in the solid state . A recent synthetic report demonstrates that similar compounds comprising {Cu 4 O 4 } rings that are capped by heterogroups can also be produced by a solvothermal reaction at a significantly lower temperature.…”
Section: Pocus Mimicking Polyoxopalladate and Polyoxoaurate Structuramentioning
confidence: 99%